2011
DOI: 10.1302/0301-620x.93b12.26985
|View full text |Cite
|
Sign up to set email alerts
|

The outcome at 20 years of conservatively treated ‘isolated’ posterior malleolar fractures of the ankle

Abstract: We assessed the long-term (20 years) outcome of closed reduction and immobilisation in 19 patients with an isolated fracture of the posterior malleolus of the ankle treated at a single hospital between 1985 and 1990. The assessments used were an Olerud functional questionnaire score, physical examination using a loaded dorsal and plantar range of movement measurement, radiological analysis of medial joint space widening, the Cedell score for anatomical alignment of all three malleoli, and the radiological pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 13 publications
(13 reference statements)
1
30
0
3
Order By: Relevance
“…1). A total of 19 studies met our inclusion criteria and were included for data analysis (Table 1) [1,6,7,11,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32]. There were five level II studies [1,19,20,26,29], 11 level III studies [6,7,12,[21][22][23]25,27,28,31,32], and three level IV studies [11,24,30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). A total of 19 studies met our inclusion criteria and were included for data analysis (Table 1) [1,6,7,11,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32]. There were five level II studies [1,19,20,26,29], 11 level III studies [6,7,12,[21][22][23]25,27,28,31,32], and three level IV studies [11,24,30].…”
Section: Resultsmentioning
confidence: 99%
“…Posterior malleolar fractures are often caused by pronation or supination external rotation trauma, also causing fracture of the lateral and medial malleolus, as described by the Lauge-Hansen classification [4]. Isolated posterior malleolar fractures are rare [5][6][7]. In current literature there is an ongoing debate on whether or not to apply osteosynthesis (internal fixation) on a posterior malleolar fragment and at which cut-off point to do this, considering its size and the amount of displacement [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,17,18 It has been reported that posterior malleolus fractures involving small fragments (up to 25% of the articular surface) present good outcomes when treated conservatively, without the need for fixation surgical procedures. [19][20][21] Nonetheless, fragments bigger than 25-30% of the articular surface and with articular incongruence (anteroposterior difference greater than 2 mm), the internal fixation of the fragment is indicated. 6,22,23 In this sense, a posterolateral approach provides a more direct access due to space created between the fibular and Achilles tendons.…”
Section: Discussionmentioning
confidence: 99%
“…Il est fonction du pourcentage de surface articulaire touchée et de la présence d'un déplacement. En effet, la présence d'une fracture marginale postérieure semble être responsable d'une augmentation significative des complications arthrosiques dans les atteintes de la pince bimalléolaire, même en cas de petits fragments marginaux postérieurs [7][8][9]. Cette fracture a donc un fort potentiel arthrogène, surtout en cas de retards diagnostique et thérapeutique, car c'est une fracture articulaire concernant un fragment osseux mal vascularisé (aucun muscle ne s'insère sur cette face postéro-inférieure du tibia).…”
Section: Discussionunclassified